Faktor yang Berhubungan dengan Tindakan PHBS pada Siswa-Siswi SD Inpres Pukdale Kecamatan Kupang Timur Kabupaten Kupang - Priscilla E.P Biri; Afrona E.L Takaeb; Eryc Z. Haba Bunga (Yayasan Literasi Sains Indonesia, 2024)
Clean and Healthy Living Behavior (PHBS) in schools is an effort to provide opportunities for students and teachers to know, want and be able to practice PHBS and actively participate in realizing healthy schools. This study aims to determine the factors related to PHBS in students of SD Inpres Pukdale, East Kupang District, Kupang Regency. This type of research is an analytical survey with a cross sectional design. The population in this study was female students SD Inpres Pukdale, East Kupang District, Kupang Regency with a total of 83 respondents. The sampling technique used is simple random sampling with a sample size of 45 respondents. The research instrument is in the form of a questionnaire. Data analysis using Chi square test with 95% confidence level (α = 0.05). The results showed that there was a relationship between knowledge variables (p-value = 0.019), attitude (p-value = 0.046), parental role (p-value = 0.070) and availability of infrastructure facilities (p-value=0.013) against PHBS actions. This study recommends that health workers provide education related to PHBS indicators in schools. Social support from parents and the school is also very necessary.